LOGISTIC REGRESSION APPROACH TO STUDY PREGNANT WOMEN CASES AS A RISK FACTOR OF LBW AT THE BATAKTE PUBLIC HEALTH CENTER, KUPANG BARAT DISTRICT - Ginting, Keristina Br; Putra, Ganesha Lapenangga (PATTIMURA UNIVERSITY, 2023)
The research examines the influencing factors of low birth weight (LBW) in the work area of ​​the Batakte Public Health Center, Kupang Regency. The specific objective of this study is to identify the risk factors associated with the LBW. In parallel with the research objective, the hypothesis of this study is that there is a relationship among several maternal factors: age, education, number of children, birth spacing, chronic energy deficiency (CED), low hemoglobin in pregnant women, and the practice of antenatal care (ANC) during pregnancy. The sample in this study was some mothers who gave birth in 2020 and 2021, whose data were recorded. The results of the study show that the logistic models of the dominant parameters causing LBW cases are: 1. Pregnant women who experience CED have a risk of giving birth to babies with LBW: 2. The risk opportunities for pregnant women with low hemoglobin (below 11g/dl) is will give birth to a LBW baby: and 3. The risk of pregnant women who never or do not routinely perform ANC is about will give birth to a LBW baby. The results of parameter interpretation show that the dominant factor causing LBW cases in the work area of the Batakte Public Health Center is pregnant women who experience chronic energy deficiency conditions, low hemoglobin, and pregnant women who have never or only once done Antenatal care (ANC) in the work area of the Batakte Public Health Center.